The Effect of the Work Environment on the Work Productivity of Nurses at Dr Tengku Mansyur Hospital, Tanjung Balai City - Handayani, Karmila Dewi; Asriwati, Asriwati; Utami, Tri Niswati; Fitriani, Arifah Devi; Anggraini, Indah (International Journal Papier Advance and Scientific Review, 2022)
Work productivity is the ratio of workers' production (output) to the capital employed (input). A worker is productive if he is able to create things or services as promised (number, quality, and completion time), yet in a short or exact amount of time and at an economical cost. The purpose of the research was to investigate the impact of the work environment on the productivity of nurses in the city of RSUD Dr. Tengku Mansyur Tanjung Balai. The study design included an analytical survey research technique (analytical research) with a cross-sectional strategy. The 156 participants in this research were all registered nurses at RSUD Dr. Tengku Mansyur Tanjung Balai City. 99 nurses were selected using a cluster random sampling method. The analysis of data included univariate, bivariate, and multivariate methods. The findings of logistic regression indicated that experience p = 0.001, career path p = 0.002, and leadership p = 0.023 were the most influential factors on the job productivity of nurses at RSUD Dr. Tengku Mangku Mangku Tanjung Balai City. This research concludes that knowledge, experience, career path, motivation, leadership, and teamwork have an effect on the job productivity of nurses at RSUD Dr. Tengku Mansyur Tanjung Balai City, with experience being the most influential variable. Suggestion made to RSUD Dr. Tengku Mansyur Tanjung Balai City to boost the job productivity of implementing nurses by improving their creativity via internal training linked to nursing care in order to achieve optimal performance.